Development and preliminary testing of a brief clinical tool to enable daily monitoring of chemotherapy toxicity: The Daily Chemotherapy Toxicity self‐Assessment Questionnaire. (11th July 2018) - Maguire, Roma; Kotronoulas, Grigorios; Donnan, Peter T.; Paterson, Catherine; McCann, Lisa; Connaghan, John; Di Domenico, David G. G.; Kearney, Nora
Abstract: Close monitoring of chemotherapy toxicity can be instrumental in ensuring prompt symptom management and quality care. Our aim was to develop a brief clinical tool to enable daily assessment of chemotherapy toxicity and investigate/establish its content validity, feasibility/applicability, internal consistency and stability. Development of the Daily Chemotherapy Toxicity self‐Assessment Questionnaire (DCTAQ) was based on an initial item pool created from two scoping reviews. Expert panel review ( n = 15) and cognitive debriefing with patients with cancer ( n = 7) were used to establish content validity. Feasibility/acceptability, applicability (self‐report vs. interview‐like administration), internal consistency (KR‐20) and test–retest reliability (at 1‐hr intervals) of the DCTAQ were field‐tested with 82 patients with breast or colorectal cancer receiving active chemotherapy at eight hospitals. Initial development/content validity stages enabled item revisions and re‐wording that led to a final, 11‐item DCTAQ version with 10 core symptom items plus one open‐ended "any other symptom" item. Feasibility and acceptability were demonstrated through the absence of participant withdrawals, absence of missing data and no complaints about tool length. The DCTAQ was found to have modest internal consistency (KR‐20 = 0.56), but very good test–retest reliability. The DCTAQ is a brief clinical tool that allows for rapid and accurate daily assessments of chemotherapy toxicity in clinical practice.